Intervensi Senam Lansia terhadap Tekanan Darah pada Lansia Hipertensi - Juli Andri; Padila Padila; Ardiansa Ardiansa; Wibowo Hanafi Ari Susanto (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2023)
This study aims to determine the classification of elderly on blood pressure in hypertensive older adults at the Tresna Werdha Social Institution, Bengkulu City. This study used a quick experiment with Two Group tests and post-test designs. The results showed a decrease in systolic and diastolic blood pressure before and after being given gymnastics for older people, with an average systolic of 143.00 mmHg to 132.73 mmHg. The dependent t-test statistical test results obtained a systolic p-value of 0.000. In conclusion, there is a significant effect between elderly exercise interventions on blood pressure in elderly hypertensives. Keywords: Hypertension, Elderly Exercise